The spatio-temporal changes of cropping patterns in the black soil area of China: Lessons from Wangkui County - Du, Guoming; Yao, Longcheng; Hou, Dawei (Frontiers in Environmental Science, 2022)
A reasonable planting crop pattern can effectively contribute to maintaining soil fertility and ensuring stable crop growth in the black soil region of China. This study aimed to analyze the evolution of cropping patterns in Wangkui county between 2002 and 2021. Throughout ArcGIS and ENVI software, we interpreted three crop rotation cycles based on the classification data of remote sensing inversion crops for 2002-2005, 2010-2013, and 2018-2021 our results indicated that maize, rice and soybean were the three major crops which accounted for a total of 87.02% farmland during our study period, while the cropping pattern was dominated by continuous maize cultivation (31.25%), mixed cultivation (29.01%) and continuous maize-soybean cultivation (24.48%). Specifically, the continuous maize cultivation was mainly distributed in the south-central and west-central parts, whereas continuous rice cultivation spread from the northwest to the southwest. In addition, the rice-soybean rotation tended to gather in the southwest and north and spread to the central part, and the rice-maize rotation presented a tendency of radiation diffusion from the county's northwest to the surrounding areas. This study could provide a practical basis for establishing high-yield and efficient planting models in the black-soil areas of China.